2020
DOI: 10.1007/s12325-020-01522-8
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Treatment of Patients with Rheumatoid Arthritis, Psoriatic Arthritis and Psoriasis in Germany: A Real-World Evidence Study

Abstract: Introduction: Rheumatoid arthritis (RA), psoriatic arthritis (PsA) and psoriasis (PSO) are chronic inflammatory diseases that have a substantial impact on patients' health. This retrospective database study aimed to assess the epidemiology, comorbidities, diagnosis and treatment patterns of RA, PsA and PSO in the German population. Methods: Data were extracted from the Deutsche Forschungsdatenbank für Abrechnungsinformationen der Krankenversicherung database from 2012 to 2016 for patients aged C 18 years holdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 45 publications
2
19
0
12
Order By: Relevance
“…Furthermore, the lower percentage of patients on biologic agents may be explained by limitations related to the prescription of these agents to patients with moderate-to-severe forms [ 16 ]. Indeed, similar proportions (0.25–2%) were observed in other studies based on claim databases [ 24 , 25 ], while a Belgian cross-sectional study that focused on moderate-to-severe PP reported that 29.5% of patients were receiving biologics [ 26 ].…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, the lower percentage of patients on biologic agents may be explained by limitations related to the prescription of these agents to patients with moderate-to-severe forms [ 16 ]. Indeed, similar proportions (0.25–2%) were observed in other studies based on claim databases [ 24 , 25 ], while a Belgian cross-sectional study that focused on moderate-to-severe PP reported that 29.5% of patients were receiving biologics [ 26 ].…”
Section: Discussionsupporting
confidence: 77%
“…Despite the high cost of this medication, a cost-effectiveness advantage of treatment with biologicals has been shown in several studies ( 24 , 25 ). Nevertheless, prescription rates of biologicals were found to be low compared with the number of eligible patients in several European countries ( 26 , 27 ). In a study from 2017, barriers to the prescription of biologicals included regulatory issues, high therapy costs, and low reimbursement for patient care for office-based dermatologists in Bavaria ( 28 ).…”
mentioning
confidence: 98%
“…Für die rheumatoide Arthritis (RA) liegen 5 Routinedatenanalysen und patientenberichtete Angaben aus der NAKO-Gesundheitsstudie vor. Die Prävalenzangaben variieren je nach Falldefinition der RA von 0,4% (Grellmann et al [6]) bis 1,85 % (selbstberichtete ärztliche Diagnose aus der NAKO-Gesundheitsstudie [4]), s. . Abb.…”
Section: Rheumatoide Arthritisunclassified